2013
DOI: 10.1021/ed300356b
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Professional Service as a Component of General Chemistry Laboratory by Demonstrating Chemistry to Elementary Students

Abstract: Formalized participation in professional service is not often part of the college experience, especially for first-year students in chemistry courses. When service opportunities are offered, they are most often through elective credit, upper-level courses, extracurricular clubs, and the rare service-learning courses. We have successfully incorporated a large science service-learning opportunity into the general chemistry laboratory that provides multidisciplinary educational experiences for children and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Not only can a well-articulated set of purposes better guide individual chapters in working toward their goals, but it can also provide an authentic and context- and research-based description of outreach goals to external stakeholders, such as funding agencies and the national organizations which support these chapters. Additionally, these purposes may help faculty in designing learning experiences and outcomes for service learning courses and/or professional service experiences …”
Section: Conclusion and Implicationsmentioning
confidence: 99%
“…Not only can a well-articulated set of purposes better guide individual chapters in working toward their goals, but it can also provide an authentic and context- and research-based description of outreach goals to external stakeholders, such as funding agencies and the national organizations which support these chapters. Additionally, these purposes may help faculty in designing learning experiences and outcomes for service learning courses and/or professional service experiences …”
Section: Conclusion and Implicationsmentioning
confidence: 99%
“…Service learning may have many descriptors (community-based learning, community-based research, civic engagement), but under any name it has been shown to engage students in applied, meaningful projects in ways that standard pedagogies generally do not . In the chemical education literature, most higher education service-learning projects fall into one of three categories, including (1) college student chemical demonstrations at K-12 schools, (2) connecting upper-level college students with high school or lower-level college students to work through an open ended problem, , or (3) college students partnering with a community organization to perform some service for the community. , In any of these contexts, the key factor is a problem with a defined goal, but an uncertain path to achieve that goal. With some guidance, students then must determine a path that can meet the goal within any imposed constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Outreach events naturally and most strongly connect with the scholarship of engagement: that is, working within one’s area of expertise and with people and institutions for the service and benefit of others. Several efforts to provide opportunities for people to explore the wonders of chemistry during NCW and at other times , illustrate this aspect of scholarship. These activities excite and inspire future chemists and scientists, educate the public, and foster collaborations between the university and the surrounding community.…”
Section: Outreach and The Various Forms Of Scholarshipmentioning
confidence: 99%